PENGARUH LIKUIDITAS, FIRM GROWTH, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Della Tantawi, Jonnardi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of liquidity, firm growth, leverage, and profitability on firm value in basic industry and chemical company listed in Indonesian Stock Exchange during the period of 2014-2018. This research used 32 companies of basic and chemical industry that have been selected using simple random sampling method. Data processing techniques in this research using Eviews 9.0 version software. The results of this research indicate that all independent variables simultaneously have a significant effect on firm value. The partialtest indicate that liquidity has no significant effect on firm value and firm growth has negative and significant effect on firm value while leverage and profitability have positive and significant effect on firm value.